Evolving strategies in the treatment of childhood rhabdomyosarcoma - Pohar-Marinšek, Živa (Radiology and oncology (Ljubljana), 2001)
Background. Neoadjuvant chemotherapy (Cht) has changed the treatment of rhabdomyosarcoma (RMS) in children. The purpose of our study was to review thechildren treated for RMS between 1974 and 1996. Patients and methods. Fifty-one children, 1-15 years old, were included. Primary sites of tumour were: head and neck 15, orbit 6, genitourinary 12, extremity 9, torso 5 and paratesticular 4. Twelve patients were in stage 1, 10 in stage II, 26 in stage111 and 3 in stage IV. Of 43 histologically confirmed RMS 25 were embryonal, 13 alveolar, 1 botryoid, 1 spindle cell and 3 sarcoma NOS. In 8 patients, only fine needle aspiration biopsy (FNAB) was available. All patients had Cht, 29 neoadjuvant, 20 had surgery first, 40 had irradiation (RT), 2 stage IV patients had bone marrow transplant (ABMT). Multidrug Cht varied: VCR, AMD, and cyclophosphamide (VAC) were used in the 1970s, with Adriablastine (T2), methotrexat (MTX) and/or other drugs (T6, T11) in the 1980s; and in the 1990s, cyclophosphamide was replaced by ifosfamide (VAIA). The treatment was started with Cht in orbital and head and neck tumours and inthe majority of genitourinary tumours, but surgery was first in paratesticular and in the majority of extremity tumours. Results. The 3 patients with stage IV disease died. Of those with localised tumour, 34 (70%) were alive and well 5 years after treatment, 80% stage I, 75% stage II and 61%stage III. One patient died of heart failure, 3 of Cht toxicity and 1 of intereurrent disease. Conclusions. (Abstract truncated at 2000 characters)
Keywords: Analiza preživetja; Child; Neoplasm staging; Novotvorba, stadij; otroci; Otrok; Rabdomiosarkom; rak (medicina); Rhabdomyosarcoma; Survival analysis; Therapy; zdravljenje